Pemberdayaan Ekonomi UMKM Brebes melalui Literasi Keuangan, Tata Kelola Syariah, dan Pendampingan Legalitas Usaha - Amelia Sholeha; Mohamad Badrun Zaman; Hilda Kumala Wulandari; Hendri Sucipto (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2026)
Low financial literacy, weak sharia-based governance, and limited business legality remain key barriers to the sustainability of Micro, Small, and Medium Enterprises (MSMEs). These constraints reduce managerial capability, restrict access to formal financing, and hinder business growth. This study developed an integrated mentoring model combining financial literacy, sharia governance, and business legalization using a Participatory Action Research (PAR) approach. 25 MSMEs in Brebes Regency participated in four stages: needs assessment, training, mentoring, and evaluation. Data were collected through pre- and post-tests, bookkeeping observations, and legality checklists. Results showed significant improvements: financial literacy scores increased from 52 to 84 (61.5%), bookkeeping adoption rose from 20% to 88%, and Business Identification Number (NIB) ownership increased from 32% to 84%. Average monthly turnover also grew by 33%. These findings indicate that participatory and practice-based mentoring effectively enhances knowledge, behavior, and economic performance. The model offers a scalable strategy for strengthening sustainable and ethical MSME management.